Effect of the interaction between Anticarsia gemmatalis multiple nucleopolyhedrovirus and Epinotia aporema granulovirus, on A. gemmatalis (Lepidoptera: Noctuidae) larvae - Biedma, Marina Elizabeth (2015)
The bean shoot borer Epinotia aporema Wals. (Lepidoptera: Tortricidae) and the velvet bean caterpillar Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) are key pests of soybean and other legume crops in South America. They are often found simultaneously in certain regions. A. gemmatalis nucleopolyhedrovirus (AgMNPV) is widely used to control A. gemmatalis. More recently, E. aporema granulovirus (EpapGV) has been characterized and evaluated as a bioinsecticide for E. aporema. In order to increase its potential use and to design optimized strategies for the management of lepidopteran pests, we evaluated the interaction between EpapGV and AgMNPV on third instar A. gemmatalis larvae. Larvae fed with 50 AgMNPV OBs/larva showed an increase in the mortality rates (from 42% to 81%) and a decrease in the median survival time (from 7.7 days to 5.7 days) when these OBs were mixed with 6000 EpapGV OBs/larva. When 300 AgMNPV OBs/larva were used alone or in combination with EpapGV OBs no changes in biological parameters were observed. No mortality was detected in A. gemmatalis larvae treated with EpapGV alone. In larvae fed with the viral mixtures, only AgMNPV DNA was detected by PCR. A. gemmatalis peritrophic membranes (PMs) examined by SDS–PAGE and scanning electron microscopy showed signs of damage. Notably, we found the presence of spheroidal bodies associated with damaged areas in the PMs of larvae fed with EpapGV but not in those that were given AgMNPV alone. These results show that EpapGV increases the viral potency of AgMNPV, and thus the insecticidal efficiency, suggesting that the use of formulations including both viruses might be a valuable tool for pest management.